2011
DOI: 10.2147/btt.s9806
|View full text |Cite
|
Sign up to set email alerts
|

Update on the use of topical calcineurin inhibitors in cutaneous lupus erythematosus

Abstract: Cutaneous manifestations of lupus erythematosus (CLE) are manifold, presenting with unspecific skin manifestations or well-defined clinical dermatological entities. Their relation to each other as well as to systemic lupus erythematosus is variable, yet diagnostically and therapeutically challenging. Therapeutic decisions have to be based on the activity and distribution as well as the type of skin lesions and the extent of systemic disease. Limited skin manifestations may be amply tackled by topical therapy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 85 publications
0
21
0
Order By: Relevance
“…11 In contrast to corticosteroids-which nonselectively affect epidermal and dermal cells-topical tacrolimus spares keratinocytes, fibroblasts, and endothelial cells, precluding the more robust adverse effects seen with corticosteroids. 12 Topical tacrolimus ointment has demonstrated mixed success in treating DLE lesions of the face and scalp as outlined in 2 in which a higherpotency tacrolimus ointment, 0.3%, was compounded with clobetasol propionate with a good clinical response. However, the inclusion of a corticosteroid obscures the precise role of tacrolimus and potentially begets a similar adverse effect profile to that of corticosteroids used alone.…”
Section: Discussionmentioning
confidence: 99%
“…11 In contrast to corticosteroids-which nonselectively affect epidermal and dermal cells-topical tacrolimus spares keratinocytes, fibroblasts, and endothelial cells, precluding the more robust adverse effects seen with corticosteroids. 12 Topical tacrolimus ointment has demonstrated mixed success in treating DLE lesions of the face and scalp as outlined in 2 in which a higherpotency tacrolimus ointment, 0.3%, was compounded with clobetasol propionate with a good clinical response. However, the inclusion of a corticosteroid obscures the precise role of tacrolimus and potentially begets a similar adverse effect profile to that of corticosteroids used alone.…”
Section: Discussionmentioning
confidence: 99%
“…13,29 Histological findings show perivascular and periadnexal lymphocytic infiltrate and the distinctive presence of mucin. Association with SLE is unusual.…”
Section: Cutaneous Lesionsmentioning
confidence: 99%
“…With their greatly reduced side-effect profile, the calcineurin inhibitors tacrolimus and pimecrolimus have emerged as effective alternatives to corticosteroids in the topical treatment of CLE [36]. A study of 38 patients showed both tacrolimus and pimecrolimus to be effective in improving symptoms of erythema, desquamation, and edema, independent of disease type [37].…”
Section: Pharmaceutical Interventionsmentioning
confidence: 99%